2016
DOI: 10.1016/j.chembiol.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Apratoxin Kills Cells by Direct Blockade of the Sec61 Protein Translocation Channel

Abstract: Apratoxin A is a cytotoxic natural product that prevents the biogenesis of secretory and membrane proteins. Biochemically, apratoxin A inhibits cotranslational translocation into the ER, but its cellular target and mechanism of action have remained controversial. Here, we demonstrate that apratoxin A prevents protein translocation by directly targeting Sec61α, the central subunit of the protein translocation channel. Mutagenesis and competitive photo-crosslinking studies indicate that apratoxin A binds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 22 publications
(30 reference statements)
10
132
1
Order By: Relevance
“…This path to incorporation of branched-chain starter units was identified recently in the annotation of gene clusters for biosynthesis of gephyronic acid (Gph) 18 and apratoxin A (Apr) 20, 21 , a Sec61 inhibitor 22, 23 . Based on the natural product structures, the AprA loading module installs a pivaloyl group, whereas GphF introduces an isobutyryl group into gephyronic acid (Figure 1a, 1b).…”
Section: Introductionmentioning
confidence: 85%
“…This path to incorporation of branched-chain starter units was identified recently in the annotation of gene clusters for biosynthesis of gephyronic acid (Gph) 18 and apratoxin A (Apr) 20, 21 , a Sec61 inhibitor 22, 23 . Based on the natural product structures, the AprA loading module installs a pivaloyl group, whereas GphF introduces an isobutyryl group into gephyronic acid (Figure 1a, 1b).…”
Section: Introductionmentioning
confidence: 85%
“…For the majority of small molecules known to modulate ER translocation, they appear to do so by acting directly at the Sec61 complex (Kalies and Römisch, 2015). Compounds such as eeyarestatin and apratoxin inhibit the Sec61-dependent translocation of a broad range of substrates (Cross et al, 2009a; Paatero et al, 2016). In contrast, and despite their common Sec61 target, HUN-7293-derived compounds such as CAM741 and the cotransin family display clear substrate specificity (Besemer et al, 2005; Garrison et al, 2005; Maifeld et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A number of small-molecule exotoxins, virulence factors, and plant secondary metabolites have been identified that inhibit protein cotranslational translocation nonselectively by binding and blocking the translocon. [45][46][47] Compounds including apratoxin A, 48 eeyerestatin I, 49 exotoxin A, 50 mycolactone, 51 ipomoeassin F, 52,53 and coibamide A 54 inhibit expression of many proteins, generally producing toxicity. A pharmacokinetic evaluation of mycolactone as a subcutaneous analgesic was recently reported.…”
Section: Substrate-nonselective Inhibitors Of Translocationmentioning
confidence: 99%
“…Resistance mutations occur in a similar area of Sec61α as for cotransin and decatransin, so it has been proposed that all of these compounds bind and act in a similar, but not identical, manner. 48 The macrocyclic triamine cyclotriazadisulfonamide (CADA) is a small molecule that inhibits replication of various strains of human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) by selectively down-modulating expression of cell-surface cluster of differentiation 4 (CD4). 27,46,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] This type 1 integral transmembrane glycoprotein is expressed on immune cells and is the primary receptor required by HIV to enter host cells.…”
Section: Substrate-selective Inhibitors Of Translocationmentioning
confidence: 99%